Effect of precursor acidity on zeolite supported Pd catalyst properties and hydrodeoxygenation activity for the production of biofuel - Ayodele, O.B.; Farouk, H.U.; Mohammed, J.; Uemura, Y.; Daud, W.M.A.W. (Elsevier, 2015)
In this study, two different zeolite (ZLT) supported palladium catalysts (Pd/Zs) of varying acidity were synthesized, characterized and tested for biofuel production. The first Pd/Z was synthesized via the incorporation of palladium oxalate complex (PdOxC) prepared from the functionalization of H2PdCl4 with oxalic acid at pH 5.3 into ZLT. The PdOxC was further modified with drops of HF until pH 3.7 and incorporated into ZLT to synthesize zeolite supported fluoride ion modified PdOxC catalyst (FPd/Z). Their characterization results showed that there is considerable crystallinity loss in Pd/Z, while FPd/Z showed drastic crystallinity loss according to the SEM and XRD results. In addition, the specific surface area and porosity of ZLT increased from 202 m(2)/g and 0.13 cm(3)/g to 371 m(2)/g and 0.23 cm(3)/g in Pd/Z, and 427 m(2)/g and 0.29 cm(3)/g in FPd/Z catalysts, respectively. Pd/Z catalyst produces 56 n-C18H38 and 11 iso-C18H38, while FPd/Z produces 58 n-C18H38 and 28 iso-C18H38 in the hydrodeoxygenation (HDO) and isomerization (ISO) steps, respectively. The enhancements in the catalysts properties are due to the acidic effect of OxA via the incorporation of PdOxC, while the additional enhancements in the properties and the ISO activity of FPd/Z was ascribed to the acidic effect of fluoride ion modification. It is obvious that OxA functionalization and subsequent fluoride ion modification are highly invaluable toward biofuel production. (C) 2015 Elsevier B.V. All rights reserved.